An empirical investigation of e-banking in the Kurdistan region of Iraq: The moderating effect of attitude - Yadgar Taha M. Hamakhan (Financial Internet Quarterly, 2020)
The banking industry is one of the most important industries in developing countries, thus it plays a major role in the financial industry. Moreover, e-banking has simplified financial transactions. This study investigates the effect of individual factors on user behaviour and the moderating effect of attitude on the relationship between individual factors and user behaviour based on the Unified Theory of Acceptance and Use of Technology. A model suggests a second-order components research framework that improves current explanations of electronic banking channel services acceptance and sheds light on the role of attitude on the acceptance of electronic banking channel services which is the most important key concern. Data were collected using an online questionnaire with 476 valid responses from academic staff who work at the University of Sulaimani; the model has been tested using the Partial Least Squares-Structural Equation Modeling approach. The results show that individual factors have a positive effect on user behaviour and also show that attitude has a negative effect on the relationship between individual factors and user behaviour as a moderator.
Keywords: G21; 330; Attitude; Individual Factors (IF); Acceptance; UTAUT; The Kurdistan Region of Iraq (KRI); Hawala